Introduction to communication electronic warfare systems - Poisel, Richard (Boston : Artech House, 2002)
Annotation This comprehensive engineering-level resource provides you with an excellent introduction to electronic warfare (EW) for communication systems. Extensively referenced with over 600 equations, it details the components, systems, and operations of electronic warfare systems dedicated to protecting and attacking military communications networks. You are provided with a complete understanding of how modern direction finders for communication signals work, along with their limitations.
8 Antennas 207 -- 8.1 INTRODUCTION 207 -- 8.2 ISOTROPIC ANTENNA 209 -- 8.3 ANTENNA GAIN 210 -- 8.4 WIRE ANTENNAS 211 -- 8.5 ACTIVE ANTENNAS 220 -- 8.6 APERTURE ANTENNAS 222 -- 8.7 GENETICALLY DESIGNED ANTENNAS 225 -- 8.8 MORE ON ANTENNA GAIN 226 -- 8.9 CONCLUDING REMARKS 228 -- References 228 -- 9 Receivers 231 -- 9.1 INTRODUCTION 231 -- 9.2 RECEIVERS 232 -- 9.3 TYPES OF RECEIVERS 246 -- 9.4 CONCLUDING REMARKS 263 -- References 264 -- 10 Signal Processing 265 -- 10.1 INTRODUCTION 265 -- 10.2 ORTHOGONAL FUNCTIONS 266 -- 10.3 TRANSFORMS 267.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Military telecommunication; Information warfare; Computer networks -- Security measures; Electronics in military engineering; Télécommunications militaires; Guerre de l'information.; Réseaux d'ordinateurs -- Sécurité -- Mesures; HISTORY -- Military -- Biological & Chemical Warfare; Computer networks -- Security measures; Electronics in military engineering; Information warfare; Military telecommunication